Exploring the Accretion Disk Structure and X-ray Radiation of GX 17+2 Based on kHz QPOs and Cross-correlations. (1st December 2022) - Wang, De-Hua; Zhang, Cheng-Min; Lei, Ya-Juan
Abstract: Applying the timing tools of kilohertz quasi-periodic oscillations (kHz QPOs) and cross-correlations, we study the influence of the magnetosphere-disk relation on the X-ray radiation process of GX 17+2. First, as the spectral state track of X-ray emission evolves along the horizontal branch (HB), the magnetosphere-disk radii of the source derived by kHz QPOs shrink from r ∼ 24 km to r ∼ 18 km, while its average X-ray intensities in ≤10 keV and in ≥10 keV show the opposite evolutional trends. Moreover, this branch has been detected with the anti-correlations between the low-/high-energy (e.g., 2–5 keV/16–30 keV) X-rays. We suggest that in HB there may exist an X-ray radiation transfer process at the disk radii near the neutron star (NS), i.e., ∼5–10 km away from the surface, which probably originates from the interaction between the corona or jet with high-energy X-rays and accretion disk with low-energy X-rays. Second, as the source evolves along the normal branch (NB) and along the flaring branch (FB), their average X-ray intensities in all ∼2–30 keV show the monotonously decreasing and monotonously increasing trends, respectively. In addition, these two branches are both dominated by the positive correlations between the low- and high-energy (e.g., 2–5 keV/16–30 keV) X-rays. Moreover, the evolution along NB is accompanied by the shrinking of the magnetosphere-disk radii from r ∼ 18 km to r ∼ 16 km. We ascribe these phenomena to that as the shrinking of the accretion disk radius, the piled up accretion matter around the NS surface may trigger the radiation that produces both the low- and high-energy X-rays simultaneously, and then form the branches of NB and FB.